La rigoladerie héroïque de Raphaël Confiant - Paraboschi, Francesca (Ponti/Ponts, 2021)
This essay analyses the plays on words in the novels by Raphaël Confiant. The writer takes on himself the heritage of orality of Martinican storytellers, rich in puns and humor. Confiant plays with the French and Creole vocabularies, but also with the forms of spoken language, such as set phrases or the network of metaphorical references, he translates from Creole into French and creating puzzling effects on the Francophone reader. The nicknames of Confiant’s heroes show the same inventing and amazing work on words the author carries on throughout his novels. He reaches the utmost effect of his esthetic in relating scenes based on misunderstandings coming forth the naivety of his heroes, quite mistaking the sense, the sound and the real meaning of some words.